2018
DOI: 10.3389/fmicb.2018.01542
|View full text |Cite
|
Sign up to set email alerts
|

Persistent and Transient Airborne MRSA Colonization of Piglets in a Newly Established Animal Model

Abstract: Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) was first found in 2005 and is up to date widespread in animal husbandry reservoir – focusing on pig farming. The regular detectability of MRSA in the air of pigsties as well as in exhaust air of pig farms (mean count: 102 cfu/m3) poses the question whether an airborne spread and, therefore, a MRSA colonization of animals via the airborne route exists. To answer this question, we exposed three groups of nine MRSA-negative tested piglets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 15 publications
2
31
1
Order By: Relevance
“…Both groups were exposed to aerosolized MRSA for 24 h using an aerosol chamber. A control group (CG) of 9 piglets (n = 9) was exposed to airborne MRSA alone as described previously [4]. All 3 groups were exposed to an airborne MRSA concentration of 10 4 cfu/m 3 as we previously demonstrated that this dose results in transient MRSA colonization of piglets [4].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Both groups were exposed to aerosolized MRSA for 24 h using an aerosol chamber. A control group (CG) of 9 piglets (n = 9) was exposed to airborne MRSA alone as described previously [4]. All 3 groups were exposed to an airborne MRSA concentration of 10 4 cfu/m 3 as we previously demonstrated that this dose results in transient MRSA colonization of piglets [4].…”
Section: Methodsmentioning
confidence: 99%
“…A control group (CG) of 9 piglets (n = 9) was exposed to airborne MRSA alone as described previously [4]. All 3 groups were exposed to an airborne MRSA concentration of 10 4 cfu/m 3 as we previously demonstrated that this dose results in transient MRSA colonization of piglets [4]. Blood samples were taken to investigate the total leucocytes, including differential blood counts and the proliferation capacity of CD 4 + T cells.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations